Post-COVID-19 syndrome and quality of life impairment in severe COVID-19 Mexican patients - Román-Montes, Carla Marina; Flores-Soto, Yesenia; Guaracha-Basañez, Guillermo Arturo; Tamez-Torres, Karla María; Sifuentes-Osornio, José; González-Lara, Ma. Fernanda; León, Alfredo Ponce de (Frontiers in Public Health, 2023)
Introduction: Post-COVID-19 Syndrome (PCS) usually occurs three months after the onset of COVID-19 with symptom duration of at least two months without an alternative diagnosis. Objective: To describe the prevalence, characteristics, and impact on Quality of life (QoL) of post-COVID-19 Syndrome in patients with a history of hospitalization for COVID-19. Materials and methods: We conducted a cross-sectional study. Patients that required hospitalization due to COVID-19 between March 2020 and October 2021 were invited to answer a PCS questionnaire and the EQ-5D instrument. Two hundred and forty-six patients were included: 187 (76%) met the definition of PCS, 54% were men, with a median age of 50 years (IQR 41-63). Results: From 187 patients with PCS, the median time to symptom onset after hospital discharge was one day (IQR 1-20), and the median symptom duration was 150 days (IQR 90-225). A total of 27 different symptoms were reported; the most frequent were difficulty concentrating (81%), dyspnea (75%), arthralgia (71%), fatigue (68%), and hair loss (60%). Some symptoms such as difficulty concentrating, arthralgia/myalgia, and hair loss, were more prevalent in women with PCS. Patients with PCS had a higher frequency of tobacco smoking (37% vs. 4%, p=0.02) and increased severity of lung involvement in the initial chest tomography (75% vs. 58%, p=0.01) compared to those without PCS. Patients with PCS were less likely to receive antivirals (15.5% vs. 27%, p=0.04). No difference between ICU admission, mechanical ventilation or length of hospital stay was found. Patients with PCS had a lower visual analog scale result for EQ-5D versus those without (80 [IQR 70-90] vs. 89.5 [IQR 75-90], p=0.05). All five QoL dimensions were affected in PCS patients, showing increased pain/discomfort (67% vs. 39%, p=<0.001), usual activities (39.2% vs. 20.3%, p=0.03) and anxiety/depression (57.5% vs. 37%, p=0.02). Conclusions: PCS occurred in 76% of hospitalized patients with prolonged duration and QoL impairment. Neurological symptoms such as difficulty concentrating were the most frequent symptom. Timely diagnostic and therapeutic interventions are required.